A Study On The Suitable Compaction Method For Physical Slope Model - Govindasamy, Darvintharen (Universiti Sains Malaysia, 2017)
Slope failure is a problem that encountered in construction of slope. One of the method to increase the strength of soil is by compaction. To ensure adequate soil compaction is achieved, the determination of optimum moisture content, maximum dry density, compaction effort, method of compaction is important. To study this problem in slope, a physical model is used with granular type of soil in it. For simplicity, the soil size was kept constant. The optimum moisture content and dry density were determined in the Standard Proctor Test. Height of 0.25 m x 1 m base and 1 m width size of soil layers are constructed in the physical model to study the compaction factors. Then, a 30° of slope with height of 0.43 m were constructed to determine the best method to build a slope in a laboratory scale. Wooden block weight of 7.5 kg with Standard Proctor rammer weight of 2.5 kg combined to complete the compaction part. The same amount of energy which is about 600 kJ used in Standard Proctor Test was applied in the study of compaction effort in the physical model. Dry compaction mainly applied in the physical model. For the height of 0.25 m, two different layers was used in the testing, which is 3 layers and 5 layers. The method of compact granular soil is kept entirely in dry condition until the necessary height is achieved then the slope should be cut because it is best to replicate the slope in a bigger scale. The density in between 3 layers and the 5 layers also varies. Thus, the fully constructed area was submerged and tested for the failure of the slope. However, no failure of slope was observed. Besides that, filling water in the physical model after compaction process also help to determine the energy distribution or compaction level between layers. If there is a line formed between soil layers, we can conclude that the amount of compaction effort not distributed uniformly.